Transformational Leadership in Practice: A Qualitative Organizational Analysis - Ramadhan, Reza Dwi; Razanah, Filda Syafira; Fadhilah, Fathin; Izzati, Umi Anugerah (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study aims to analyze the application of transformational leadership style in improving employee performance through an organizational diagnosis approach at PT X. Design/method/approach – The article uses a descriptive qualitative method with data collection techniques in the form of in-depth interviews, participatory observation, and document analysis to obtain a comprehensive picture of the leadership patterns applied. The analysis was conducted using an organizational diagnosis framework that covers four main aspects: organizational structure, task distribution, technology utilization, and human resource management. Findings – Results show that the application of transformational leadership by leaders at PT X has a significant impact on increasing work motivation, organizational commitment, and individual effectiveness in task execution. Leaders who are able to act as inspirers, facilitators, and role models have been proven to encourage more positive work behavior, strengthen team collaboration, and increase orientation towards common goals. Implications – The study provides practical insights for organizations in designing more adaptive and change-oriented managerial strategies, particularly in the context of organizations in Indonesia. Novelty/Originality – This research provides an initial contribution to the discourse on contextual leadership in Indonesian organizational environments and serves as a basis for the development of leadership approaches that are more responsive to organizational dynamics.